UNVEILING THE ENIGMA OF LOCAL WISDOM-BASED TOURISM DEVELOPMENT IN SUROWITI VILLAGE, GRESIK REGENCY - Rosyanafi, Rofik Jalal; Roesminingsih, Maria Veronika; Susilo, Heryanto; Nusantara, Widya; Harris, Taufiq (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
Within the framework of community empowerment and sustainable development, this study presents a novel model for harnessing the potential of village tourism in Surowiti Village, Gresik Regency. The model pivots on the exploration of local wisdom to engender an authentic and sustainable tourism ex- perience. Employing a qualitative approach through in-depth interviews and participatory observation, this research illuminates the substantial existence of a rich reservoir of local wisdom, encompassing traditions, culture, and sustainable practices, that endures within Surowiti Village. The proposed village tourism development model adeptly interweaves constituents of local wisdom into the tourism experi- ence, yielding palpable positive ramifications for both the local populace and the surrounding environ- ment. The implications of this study underscore the pivotal importance of fostering local community empowerment, preserving cultural heritage, and advocating for sustainable tourism promotion. The model proffered herein exhibits substantial potential for adoption by diverse communities and govern- mental bodies in their pursuit of cultivating enduringly sustainable village tourism, yielding significant positive socio-economic impacts.